1992
DOI: 10.1039/ft9928802459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protonation on acetone: nuclear magnetic resonance and ab initio studies

Abstract: The electronic and geometric structural changes of acetone upon protonation are studied by 3C NMR spectroscopy and by molecular orbital (MO) calculations using the LORG (local orbital/local origin) method to calculate chemical shieldings and the CLOPPA (contributions for localized orbitals within the polarised propagator approach) analysis of the J coupling constants. In protonated acetone the 13C NMR spectrum has been resolved and two different methyl resonances (1.2 ppm apart) have been assigned. The one-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Calculated gas-phase structures of acetone, protonated acetone, and a hydrogen-bonded acetone dimer are reported in Figure . The internal coordinates for acetone in Figure are consistent with those in earlier work and in a recent report for acetone optimized at MP2/tzp; and a frequency analysis shows that the minimum-energy geometry has C 2 symmetry. The calculated proton affinity of acetone at MP2/6-311+G* is 185.4 kcal/mol.…”
Section: Theoretical Resultssupporting
confidence: 88%
“…Calculated gas-phase structures of acetone, protonated acetone, and a hydrogen-bonded acetone dimer are reported in Figure . The internal coordinates for acetone in Figure are consistent with those in earlier work and in a recent report for acetone optimized at MP2/tzp; and a frequency analysis shows that the minimum-energy geometry has C 2 symmetry. The calculated proton affinity of acetone at MP2/6-311+G* is 185.4 kcal/mol.…”
Section: Theoretical Resultssupporting
confidence: 88%
“…The first observation of the lone pair effect on 1 J(C,C) coupling constants was report for a series of oximes including the title compound ethanaloxime [69]. Previous semi-empirical [85,86] and DFT [79] calculations on acetoxime as well as DFT [78] and SOPPA(CCSD) [16] calculations on methanimine showed that only the FC contribution is changed by the lone pair effect. Furthermore an analysis of the contributions of individual localized DFT molecular orbitals to the FC term in the same molecules [78,79] indicated that this effect is primarily due to a direct lone pair contribution from the corresponding localized orbital, which is positive for the coupling synperiplanar to the lone pair and negative for the coupling antiperiplanar to it.…”
Section: One-bond Couplingmentioning
confidence: 99%
“…We start this section with the discussion of the so-called "lone pair effect", originally reviewed by Gil and von Philipsborn. [231] The Lone Pair Effect (LPE) was reported for carbon-carbon coupling constants as early as in 1984, [232] which further received its theoretical explanation in the papers by Contreras, et al [233][234][235][236][237] The application of LPE opened a new guide for the stereochemical assignment of imines and related molecules. [238][239][240][241][242][243] In a continuation of those studies, this effect was also documented and theoretically interpreted for carbonhydrogen coupling constants (Scheme 9) which is discussed in more detail below.…”
Section: Functional Derivativesmentioning
confidence: 99%